Salinity induced oxidative stress alters the physiological responses and improves the biofuel potential of green microalgae Acutodesmus dimorphus. (November 2017) - Chokshi, Kaumeel; Pancha, Imran; Ghosh, Arup; Mishra, Sandhya
Highlights: Salinity induced oxidative stress improved the biofuel potential of A. dimorphus. Addition of 200 mM NaCl increased the lipid and carbohydrate accumulations over 50%. Salinity stress of 200 mM for 2 days increased the biomass of A. dimorphus. Oxidative stress biomarkers were the lowest in 2 days stressed culture. 3 days of stress increased lipid accumulation by 43% without affecting the biomass. Abstract: The main aim of the present study was to analyze salinity stress induced physiological and biochemical changes in a freshwater microalgae Acutodesmus dimorphus . During single-stage cultivation, the accumulations of lipids and carbohydrates increased with an increase in an initial salinity of the culture medium. The carbohydrate and lipid accumulations of 53.30 ± 2.76% and 33.40 ± 2.29%, respectively, were observed in 200 mM NaCl added culture. During two-stage cultivation, salinity stress of 200 mM was favorable for the growth up to 2 days, as suggested by higher biomass, lower levels of oxidative stress biomarkers and no significant changes in the biochemical composition of the cells. Extending the stress to 3 days significantly increased the lipid accumulation by 43% without affecting the biomass production. This study, thus, provides the strategy to improve the biofuel potential of A. dimorphus along with presenting the physiological adaptive mechanisms of a cell against salinity stress.